Rancang Bangun Aplikasi Pendukung Media Pembelajaran Advanced Communicative Grammar Skill Berbasis Android Pada Program Studi Pendidikan Bahasa Inggris S1 Uny - Reza, Tan Muhammad; Sutarman , Sutarman (Syntax Corporation, 2025)
The teaching of English grammar often poses a significant challenge for university students, particularly in developing effective academic communication skills. Conventional grammar instruction, which predominantly relies on printed textbooks, tends to be less interactive and does not sufficiently promote autonomous learning. Therefore, there is a growing need for technological innovations in instructional media that can facilitate a more flexible, engaging, and academically relevant learning process. This study aims to design and develop an Android-based learning application entitled Advanced Communicative Grammar Skills, integrated with the lecturer’s website, to enhance students’ learning effectiveness, flexibility, and engagement in higher education contexts. The research employed the ADDIE development model, encompassing five stages: Analysis, Design, Development, Implementation, and Evaluation. The usability testing phase utilized the System Usability Scale (SUS) involving 12 undergraduate students and 2 lecturers from the English Education Study Program, Universitas Negeri Yogyakarta. The results of the usability testing revealed that students rated the application with an average score of 77.17 (Grade B), indicating that it is feasible for use as an interactive learning medium. Meanwhile, the lecturers’ initial evaluation produced an average score of 46.25 (Grade D). After revisions and the integration of additional features based on the lecturers’ recommendations, the satisfaction score increased significantly to 82.5 (Grade A). This finding demonstrates that the subsequent development phase effectively improved both the feasibility and user satisfaction from the lecturers’ perspective.In conclusion, the Advanced Communicative Grammar Skills application has been successfully developed as a viable and effective digital learning medium to support English language instruction in higher education. This innovation addresses the need for a flexible, interactive, and integrated learning platform that bridges students and lecturers in communicative grammar learning.